In situ measurement of the effective nonlinear absorption order in multiphoton photoresists. Issue 5 (7th September 2016) - Tomova, Zuleykhan; Liaros, Nikolaos; Gutierrez Razo, Sandra A.; Wolf, Steven M.; Fourkas, John T.
Abstract : Multiphoton absorption polymerization is used widely for fabricating 3D microstructures. Being able to make in situ measurements of the order of the effective nonlinear absorption is crucial for the development of improved multiphoton photoresists. An easily implemented method is presented for the unambiguous determination of the order of effective nonlinear absorption without having to vary the laser repetition rate or exposure time. Abstract: Knowledge of the order of the effective nonlinear absorption in multiphoton photoresists is a key element in the development of improved materials for multiphoton absorption polymerization (MAP). The direct measurement of this nonlinearity has proven challenging. A new technique called 2‐beam initiation threshold (2‐BIT) is presented that allows for the unambiguous, in situ measurement of the order of the effective nonlinear absorption using a simple optical arrangement that can be employed with virtually any MAP setup. This technique is benchmarked using three common commercial photoinitiators that have been used previously in MAP and one common dye that acts as a photoinitiator. The linear absorption spectrum is demonstrated to be a poor predictor of the effective order of nonlinear absorption at a given wavelength. Surprisingly, for two of these initiators the effective nonlinear absorption process is dominated by 3‐photon absorption in the 800 nm wavelength range, suggesting that 2‐BIT is a valuable means of identifying initiators that can improve the resolution of MAP.